Penetrating Keratoplasty Following Superficial Keratectomy, Amniotic Membrane Patch and Bandage Soft Contact Lenses in Band and Pseudophakic Bullous Keratopathy - Rachmawati Samad; Junaedi Sirajuddin; Hasnah B. Eka (Majalah Oftalmologi Indonesia, 2021)
Introduction: Band keratopathy is usually associated with chronic ocular inflammatory conditions. Recent use of combination treatments such as chelation,excimer laser,and amniotic membrane transplantation in band keratopathy management. Bullous keratopathy (BK) is a main complication of cataract surgery.The purpose of treatment are to reduce pain and improve vision when possible. Treatment depending on the severity of symptoms,cause of BK and potential for visual improvement. BK is a leading indication for keratoplasty and improvement of vision is possible only with keratoplasty. Objective: To report a case of a 64-year-old man with penetrating keratoplasty (PK) following superficial keratectomy (SK), amniotic membrane patch (AMP) and bandage soft contact lenses (BSCL) in band and pseudophakic bullous keratopathy. Case presentation: A 64-year-old man with band and pseudophakic bullous keratopathyreported with reduced vision in both the eyes (1/300 and 6/48 BCVA in the right and left eye, respectively) for past few years.SK, AMP and BSCLwas performed for ocular surface reconstruction in his right eye. One month later, he underwent a PK and3 months following surgery, the corneal graft remained transparent. Six months after the surgery, BCVA of the right eye was 6/30 with S - 3,00 refractive correction. Conclusion: Patients with band and pseudophakic bullous keratopathy can achieve visual outcomes and realise a significant improvement in corneal transparency by undergoing SK, AMP, BSCL and PK.